(untitled) (Clinics, 2013)
OBJECTIVE: To investigate the influence of (CA)n repeats in the insulin-like growth factor 1 gene and a variable number of tandem repeats of the insulin gene on birth size in children who are small or adequate-sized for gestational age and to correlate these polymorphisms with serum insulin-like growth factor 1 levels and insulin sensitivity in children who are small for gestational age, with and without catch-up growth. PATIENTS AND METHODS: We evaluated 439 infants: 297 that were adequate-sized for gestational age and 142 that were small for gestational age (66 with and 76 without catch-up). The number of (CA)n repeat in the insulin-like growth factor 1 gene and a variable number of tandem repeats in the insulin gene were analyzed using GENESCAN software and polymerase chain reaction followed by enzymatic digestion, respectively. Clinical and laboratory data were obtained from all patients. RESULTS: The height, body mass index, paternal height, target height and insulin-like growth factor 1 serum levels were higher in children who were small for gestational age with catch-up. There was no difference in the allelic and genotypic distributions of both polymorphisms between the adequate-sized and small infants or among small infants with and without catch-up. Similarly, the polymorphisms were not associated with clinical or laboratory variables. CONCLUSION: Polymorphisms of the (CA)n repeats of the insulin-like growth factor 1 gene and a variable number of tandem repeats of the insulin gene, separately or in combination, did not influence pre- or postnatal growth, insulin-like growth factor 1 serum levels or insulin resistance.